Analisis Keterlambtan Proyek Pembangunan Pemeliharaan Berkala Jalan Cut Nyak Dien (No. Ruas 44) Kota Probolinggo dengan Menggunakan Earned Value Method (EVM) - Taqwa, Nurul; Yusuf, Andrian Firdaus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The importance of highway infrastructure is crucial for the transportation system, supporting economic growth and community mobility through increased accessibility and socio-economic development. This qualitative research analyzes the delays in the Cut Nyak Dien road periodic maintenance project in Probolinggo City, focusing on service, cost, and implementation time. The main objective is to identify dominant factors such as inadequate planning, bad weather, financing problems, and weak management, and to design effective management strategies to mitigate their impacts. The case study method is used to dig up in-depth data, supported by earned value for project performance evaluation and Microsoft Project for data analysis. The results are expected to provide practical recommendations for the Probolinggo City Government, especially in preparing the budget for campus development towards PTNBH, as well as other infrastructure construction management accounts to improve cost and time efficiency.